ผลการใช้โปรแกรมการช่วยเหลือตนเองโดยการฟังเพื่อพัฒนาความคิดเชิงบวกของวัยรุ่นที่พิการทางการมองเห็น (THE EFFECTS OF SELF - HELP AUDIO PROGRAM ON POSITIVE THINKING DEVELOPMENT OF ADOLESCENTS WITH VISUAL DISABILITIES) - กมลบาล, ศิริชัย กมลบาล; สู้รักษา, นันทา; ศรีวันยงค์, ศิริพันธ์ (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2015)
บทคัดย่อ การศึกษาครั้งนี้มีความมุ่งหมายเพื่อศึกษาผลการใช้โปรแกรมการช่วยเหลือตนเองโดยการฟังเพื่อพัฒนาความคิดเชิงบวกของวัยรุ่นที่พิการทางการมองเห็น ประชากรเป็นนักเรียนวัยรุ่นที่พิการทางการมองเห็นโรงเรียนสอนคนตาบอดกรุงเทพ จำนวน 89 คน กลุ่มตัวอย่างที่เข้าร่วมโปรแกรมการช่วยเหลือตนเองโดยการฟังเพื่อพัฒนาความคิดเชิงบวกเป็นนักเรียนที่มีคะแนนความคิดเชิงบวกตั้งแต่เปอร์เซ็นไทล์ที่ 25 ลงมา โดยมีความสมัครใจในการเข้าร่วมโปรแกรม จำนวน 8 คน เป็นนักเรียนชาย จำนวน 4 คน และนักเรียนหญิง จำนวน 4 คน เครื่องมือที่ใช้ในการศึกษา ได้แก่ แบบสอบถามความคิดเชิงบวก และโปรแกรมการช่วยเหลือตนเองโดยการฟังเพื่อพัฒนาความคิดเชิงบวกของวัยรุ่นที่พิการทางการมองเห็น สถิติที่ใช้ในการวิเคราะห์ข้อมูลคือ t-test Independent และ ANNOVA ผลการวิจัยพบว่า 1) ความคิดเชิงบวกของวัยรุ่นที่พิการทางการมองเห็น จำแนกตามเพศ อายุ ลักษณะของความพิการทางการมองเห็น และระยะเวลาที่พิการทางการมองเห็นไม่แตกต่างกัน ทั้งในภาพรวมและรายด้าน 2) นักเรียนวัยรุ่นที่พิการทางการมองเห็นที่เข้าร่วมโปรแกรมการช่วยเหลือตนเองโดยการฟัง มีความคิดเชิงบวกเพิ่มขึ้นอย่างมีนัยสำคัญทางสถิติที่ระดับ 0.01 Abstract The objective of this research was to study the effects of self-help audio program on positive thinking development of adolescents with visual disabilities. Research population includes a group of eighty-nine adolescents with visual disabilities from The Bangkok School for the Blind. The subjects were 4 males and 4 females students whose initial test scores were lower than the percentile rank of 25. The instruments used in the research consisted of positive thinking questionnaire on and the Positive thinking development audio program. T-test Independent and ANNOVA were used to analyze data. The results were as follows. 1) The distinctiveness of neither the physical condition nor disability level of the adolescents with visual disabilities, including gender, nature of disability and the duration of disability, were not have a significant differences on positive thinking of adolescents with visual disabilities for overall and different aspects. 2) There was a statistically significance difference in positive thinking of adolescent students after participated in self-help audio program, positive thinking of adolescents increase by having Statistical significance of 0.01.